Development of a mini pig model of peanut allergy - Shakya, Akhilesh Kumar; Backus, Brittany; Nesovic, Lazar D.; Mallick, Malini; Banister, Olivia; Davis, Carla M.; Anvari, Sara; Gill, Harvinder Singh (Frontiers in Allergy, 2024)
Introduction The prevalence of peanut allergies is increasing, emphasizing the need for an animal model to enhance our understanding of peanut allergy pathogenesis and to advance diagnostic tools and therapeutic interventions. While mice are frequently used as model organisms, their allergic responses do not fully mirror those observed in humans, warranting the exploration of a higher animal model. The porcine gastrointestinal system closely resembles that of humans, and exhibits allergy symptoms akin to human responses, making pigs a promising model for peanut allergy research. Methods In this study we compared two allergen sensitization protocols involving either topical allergen application after repeated tape stripping (TS) or intraperitoneal (IP) injections to induce peanut-specific allergy and anaphylaxis reactions in mini pigs. Mini pigs sensitized with a combination of peanut protein extract (PE) and cholera toxin (CT) through either the IP or the TS route. Results Sensitized pigs via both methods developed systemic PE-specific IgG and IgE responses. Following peanut challenge via the IP route, both TS- and IP-sensitized pigs displayed allergy symptoms, including lethargy, skin rashes, vomiting, and a drop in body temperature. However, respiratory distress was observed exclusively in pigs sensitized through the TS route and not in those sensitized through the IP route. However, it is noteworthy that both groups of sensitized pigs maintained peanut hypersensitivity for up to two months post-sensitization, albeit with a reduction in the severity of allergy symptoms. Importantly, both groups exhibited sustained levels of PE-specific IgG, IgE, and elevated concentrations of mast cell protease in their blood following the IP challenges. Discussion Overall, this study reports TS and IP as two different modes of sensitization leading to onset of peanut specific allergic reactions in mini pigs, but only the TS-sensitization led to systemic anaphylaxis (simultaneous presence of symptoms: breathing difficulty, intense skin rash, and impaired mobility). A distinctive feature of these sensitization protocols is the 100% success rate (N = 4 pigs per group) in sensitizing the subjects.